STRATEGI PENGEMBANGAN PARIWISATA BERBASIS POTENSI LOKAL DI KECAMATAN MEDAN SELAYANG - Ndruru, Yulianus Juniato; Zafira Amanda (PT. Arsil Reka Engineering, 2024)
The tourism in the Selayang Medan sub-district is included as one of the sub-districts that has several tourist attractions. When viewed from the number of residents, Traveler especially the city of Medan, have increased from year to year. tourism in the Medan Selayang sub-district continues to be planned to attract more visitors, therefore this research is carried out by analyzing problems and solutions in developing tourism in the Medan Selayang sub-district, such as data collection and tourist objects and attractions in the Medan Selayang sub-district, Analyzing tourism conditions related to issues as well as tourism potential and problems in the Medan Belawan sub-district, and proposed tourism development for the Medan Selayang sub-district. The method used in this research is a qualitative method with a data search process that is carried out by means of literature studies through books, related research journals and through internet pages. The final result of this study is the identification of proposals for maximizing and improving facilities as tourism development in the Medan Selayang.